The Contribution of Language Input, Conducive Learning Environment, and Motivation toward Student’s Speaking Proficiency - Azhimia, Faida; Parnawati, Tantry Ajeng (Journal of Language Intelligence and Culture, 2023)
This study aimed to identify student’s speaking proficiency through the contribution of language input, conducive learning environment, and motivation. This research is qualitative study. Using a case study approach, the research sample consist of a single university student majoring in Business and Management, selected through purposive convenience sampling. Data was collected through interview, which explored student’s speaking ability, the availability of language input, learning environment, and student’s motivation. The findings reveal that the student demonstrated a good level speaking proficiency. Notably, subject's motivation affects her speaking proficiency more than the other aspects; language input and learning environment. Although the student’s exposure to language input is moderate, the learning environment is found as poor. To conclude, the three aspects of language learning: language input, learning environment, and motivation, affect student’s speaking proficiency. The outcomes portray the common experiences of Indonesian language learners as they acquire English as second language.